Efek Antiangiogenik Ekstrak Etanol Buah Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl.) pada Membran Korio Alantois (CAM) Embrio Ayam - Roat Yeti Mustafida; Al Munawir; Rosita Dewi (Pustaka Kesehatan, 2014)
Angiogenesis is the growth of new blood vessels that are used to supply nutrients and oxygen including cancer cells. Phaleria macrocarpa contains tannin, saponin, alkaloid, and flavonoid, known as an antiangiogenesis. This study determined the antiangiogenic effects of ethanolic extract of Phaleria macrocarpa on chorio allantoic membrane of chicken embryos. The antiangiogenesis trials used chorio allantoic membrane of 9 days chicken embryos. There were 5 groups, negative control group [K(-)] and 4 treatment groups (P), each group containing 4 eggs. K(-) group using aquadest and tween 80%; P groups with ethanolic extract of Phaleria macrocarpa at a concentration 10 ug/µL, 40 ug/µL, 80 ug/µL, 160 ug/µL for P1, P2, P3, dan P4 respectively. The number of new blood vessels on chorio allantoic membrane were K(-): (42.5 ± 14.57), P1: (28.25 ± 3.59), P2: (28.5 ± 1.73), P3: (15 ± 4.32), and P4: (6.5 ± 1.73). In conclusion, the ethanolic extract of phaleria macrocarpa has an antiangiogenic effect on chorio allantoic membran by decreasing the number of new blood vessels.Keywords: angiogenesis, Phaleria macrocarpa, ethanolic extract, chorio allantoic membrane